Pattern of Suicidal Deaths in the First Month of Lockdown at A Tertiary Care Hospital: a Time Trend Analysis - Deepmalya Sengupta1 , Saikat Saha2 , Pranabesh Bharatee2 , Rajib Prasad3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Lockdowns and quarantines were set up in various countries around the world to combat the Corona viruspandemic. The pandemic has its mental health consequences which have been aggravated by the lockdownmeasures. The resulting psychological distress and depression has ultimately led to suicides. This studyexplores the trends of suicide in the month of the lockdown and compared it with those to the prior months.The study was conducted between 25th January 2020 to 24th April 2020 and March 25th 2019 to April 24th2019 at Cooch Behar Government Medical College and Hospital, Cooch Behar. 52.1% cases of suicide wererecorded in the month of lockdown which increased from 34.1% in February 2020 and 43.1% in March2020. Most cases of suicide in the period of lockdown were in the second and third decade of life with amale predominance. For the period of lockdown, housewives, businessmen and labourers were found out tobe the vulnerable population. A social and public health response in addition to a mental health response iscrucial to prevent suicidal behaviour in lockdown period